An Overview Risk Factors for Pneumonia in Pre-school Children - Artawan, I Kadek; Sastrayanti, Ni Wayan Ardiana; Remiyasa, I Wayan (Journal of Language and Health, 2025)
Pneumonia is an acute infection affecting the lung tissue (alveoli) caused by various microorganisms, including viruses, fungi, and bacteria. One of the risk factors is the presence of polluted air, an unhealthy environment that increases children's exposure to bacteria and viruses due to the polluted environment. If this condition continues, it will cause various impacts until death. The general objective in conducting this study was to determine the overview of risk factors causing pneumonia in pre-school children. This study used a descriptive method with a quantitative approach, the sampling technique used in this study was Accidental sampling, with a population of 186 and a sample size of 127 respondents. The research instrument used was a questionnaire. The questionnaire contained 10 questions about 10 indicators of PHBS. The data was then analysed by univariate analysis. The results of research from 127 respondents, namely from the number of 10 indicators of PHBS, the highest number of not done is consuming fruit and vegetable foods every day, namely as many as ‘yes’ 72 (56%), ‘no’ 55 (43%). Of the 10 indicators of PHBS, the most common risk factor for pneumonia is not eating fruits and vegetables, so monitoring the nutritional status of toddlers is the most important and main concern to prevent pneumonia.